2019
DOI: 10.1186/s12882-019-1617-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular resistance is increased in patients with kidney transplant

Abstract: BackgroundDespite improvement in short-term outcome of kidney transplants, the long-term survival of kidney transplants has not changed over past decades. Kidney biopsy is the gold standard of transplant pathology but it’s invasive. Quantification of transplant blood flow could provide a novel non-invasive method to evaluate transplant pathology. The aim of this retrospective cross-sectional pilot study was to evaluate positron emission tomography (PET) as a method to measure kidney transplant perfusion and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…AR is typically diagnosed by increased serum creatinine concentration (Scr), decreased glomerular filtration rate (GFR), changes in urine volume, and biopsy (19,20). Unfortunately, these indicators are delayed and insensitive biomarkers of AR (21)(22)(23)(24), usually reflecting a late sign of kidney damage. Therefore, the identification of more sensitive and specific biomarkers for the early diagnosis of acute renal rejection is imperative (19).…”
Section: Introductionmentioning
confidence: 99%
“…AR is typically diagnosed by increased serum creatinine concentration (Scr), decreased glomerular filtration rate (GFR), changes in urine volume, and biopsy (19,20). Unfortunately, these indicators are delayed and insensitive biomarkers of AR (21)(22)(23)(24), usually reflecting a late sign of kidney damage. Therefore, the identification of more sensitive and specific biomarkers for the early diagnosis of acute renal rejection is imperative (19).…”
Section: Introductionmentioning
confidence: 99%
“…RI can also be reliably measured in renal grafts if accessible (25). Päivärinta et al assessed the kidney function with PET-CT and RI measurements with CCDS to show that the RI was correlated with perfusion and fibrosis of the transplants (26). Boran et al found an association between recipients with proteinuria <1,000 mg/24 h, and elevated RIs (27).…”
Section: Discussionmentioning
confidence: 99%
“…assessed the kidney function with PET-CT and RI measurements with CCDS to show that the RI was correlated with perfusion and brosis of the transplants [22]. Boran et al found an association between recipients with proteinuria < 1000 mg/24 h, and elevated RIs [23].…”
Section: Discussionmentioning
confidence: 99%